Factors influencing motivation of women social entrepreneurs in the Lundu District, Sarawak, Malaysia - Yee, Lai Ling (2019)
Social entrepreneurship has been gaining the attention from both scholars and practitioners due to its effectiveness as a tool in solving social issues and uplifting the quality of life of community, especially from the aspects of social, economic, and environmental. The concept of social entrepreneurship is composed of the use of conventional business model to achieve social mission addressed by the social entrepreneurs. The study site of this study, Lundu District of Kuching has been approved by the Sarawak Government to be transformed into an ecotourism hub. Thus, it has the great potential for the local communities to venture as social entrepreneurs while embracing certain social mission that they wish to improve on. However, to date, there are still limited people joined. Since women proved to have higher participation in social entrepreneurship, the objectives of this study are to identify the profile of existing women social entrepreneurs in Lundu District, their business information, their motivation to join, and the factors that influence their motivation. A quantitative study with validated questionnaire has been conducted. Prior the real data collection, a pilot study has been carried out to ensure the reliability of the instrument. Data collected from 150 women social entrepreneurs in Lundu District was analysed through IBM SPSS Statistics Version 23. Descriptive and multiple linear regression analysis were used to answer the objectives of this study. Results showed that women social entrepreneurs in Lundu District are of various background. Generally, the women social entrepreneurs are positively motivated by all of the eight motivational dimensions tested in the study, in the order of Financial Motivation, Desire to Contribute to Community, Need for Affiliation, Need for Achievement, Empathy, Need for Power, Past Volunteerism Experience, and lastly, the Role Models Influence. From the socio-demographic characteristics and business information tested, attended courses and training, social missions (participation of women and youth in the workforce, older persons, education, nature and living environment, children, disability, productive income, and culture), education level (no formal education), SDSI clusters (food/beverage products cluster and craft products cluster), Malay ethnic, and Lundu village are the factors that found to be affected the motivation of women social entrepreneurs in Lundu District. The findings of this study can be referred by policy-makers to design strategies to encourage more people to join the beneficial venture of social entrepreneurship. This study has closed the gaps in the literature regarding the social entrepreneurship motivation specifically in the setting of ecotourism site. While the framework used in this study is proved to be accepted by the analysis conducted, it can be adopted in future studies to test its generality on other background settings.